All-dielectric chiral-field-enhanced Raman optical activity - Ting-Hui Xiao (Nature Portfolio, 2021)
Raman optical activity (ROA) is useful for studying conformational structure and behavior of chiral molecules, but is limited by the weak signals. Here, the authors demonstrate 100x signal enhancement via an all-dielectric approach, using a silicon nanodisk array and exploiting its dark mode.